Chapter 3: A Dialogue: Ethics, Law, and the Question of Detention in Non-International Armed Conflicts. (2nd February 2015) - Johnson, James Turner
Abstract: This chapter begins with the observation that non-international armed conflicts pose serious challenges to the efforts to regulate war in both international law and recent ethical discourse, and argues that neither has responded well to these challenges. Various problems in both are identified. The second part of the chapter examines the historical conception of just war accepted as consensual in the West from the high Middle Ages till early in the modern period, arguing that it provides a helpful frame for thinking ethically about non-international armed conflicts. The third section of the chapter carries this reasoning forward, applying it to non-international armed conflicts generally and to the problem of detention in such conflicts specifically.